2016
DOI: 10.1259/bjr.20150725
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging features of a subchondral insufficiency fracture of the femoral head after internal fixation of a femoral neck fracture: a comparison with those of post-traumatic osteonecrosis of the femoral head

Abstract: SIF should be considered a possible condition following the internal fixation of FNFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
6
0
5
Order By: Relevance
“…[2][3][4] Recently, it has been recognized to be associated with not only systemic osteoporosis but also local osteopenia of the hip joint, as well as activity fatigue type of fracture, even in young patients. [7][8][9][10] We demonstrated that pediatric patients could have this type of fracture, in which detailed radiological findings had not been reported. These patients were diagnosed based on radiological evidence of a fracture line in living bone confirmed with contrast-enhanced MR images and clinical evidence of a fracture healing process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Recently, it has been recognized to be associated with not only systemic osteoporosis but also local osteopenia of the hip joint, as well as activity fatigue type of fracture, even in young patients. [7][8][9][10] We demonstrated that pediatric patients could have this type of fracture, in which detailed radiological findings had not been reported. These patients were diagnosed based on radiological evidence of a fracture line in living bone confirmed with contrast-enhanced MR images and clinical evidence of a fracture healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of subchondral fracture of the femoral head has still been unclear, systemic and local osteopenia are known to be significant risk factors. [7][8][9] Recently, pelvic anatomical abnormalities, such as acetabular retroversion and asphericity of femoral headneck junction, were also reported to be associated with patients with this condition. 20 Case 1 in the present report had bilateral acetabular retroversion, while case 2 demonstrated local osteopenia in the left hip due to a long-term Journal of Orthopaedic Surgery 28 (2) nonweight-bearing in addition to coxa magna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le traitement des fractures fémorales consiste en une réduction anatomique et, d'emblée, la réalisation d'une ostéosynthèse stable [8]. En deçà de 70 ans et en présence d'une bonne qualité osseuse c'est l'ostéosynthèse qui prime [8,35]. En effet, du point de vue biomécanique, il est avantageux de conserver la hanche native, cette dernière étant plus adaptée aux exigences fonctionnelles des sportifs [8].…”
Section: Traitementunclassified
“…1,10,11 ONFH is a devastating and progressive disease, which, if left untreated, will cause the collapse of the femoral head. 12,13 Consequently, approximately 70% of patients need hip replacement. 14- 16 While existing theories have pointed to the roles of intravascular coagulation and fat embolism as well as extravascular fat accumulation-mediated vascular constriction in the pathogenesis of ONFH, 17 the exact mechanism is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%